2004
DOI: 10.1016/j.jacc.2003.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Novel and traditional cardiovascular risk factors in children after Kawasaki disease

Abstract: An adverse cardiovascular risk profile, as characterized by a proatherogenic alteration of the lipid profile and increased arterial stiffness, occurs in children after KD. The profile is worse in those with than in those without coronary aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 29 publications
12
113
1
3
Order By: Relevance
“…Therefore, we cannot exclude the possibility that the present sample sizes were not sufficient to allow detection of differences in characteristic impedance and C/BSA between the 2 KD groups. Although several previous hemodynamic and histopathologic studies 32,35,44 suggested that arterial stiffness increases regardless of coronary artery involvement, which is consistent with the present results (no difference in characteristic impedance or C/BSA between groups 1A and 1B), further studies clearly are needed to confirm the present findings.…”
Section: Study Limitationssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we cannot exclude the possibility that the present sample sizes were not sufficient to allow detection of differences in characteristic impedance and C/BSA between the 2 KD groups. Although several previous hemodynamic and histopathologic studies 32,35,44 suggested that arterial stiffness increases regardless of coronary artery involvement, which is consistent with the present results (no difference in characteristic impedance or C/BSA between groups 1A and 1B), further studies clearly are needed to confirm the present findings.…”
Section: Study Limitationssupporting
confidence: 92%
“…Noto et al 31 showed increased carotid arterial stiffness in 20 KD patients with CAL using a stiffness index based on ultrasonographic measurements. Cheung et al 32 observed increased pulse-wave velocity (a measure of arterial stiffness) in the brachioradial artery of KD patients with and without CAL. The present data demonstrate several novel aspects of systemic arterial stiffening after KD.…”
Section: Arterial Stiffening After Kdmentioning
confidence: 99%
“…227 In addition, Kawasaki disease produces altered lipid metabolism that persists beyond clinical resolution of the disease. 75,77,228 Children with Kawasaki disease with normal coronary arteries also have been reported to have higher brachial-radial artery mean pulse wave velocity than do children without Kawasaki disease, suggesting increased arterial stiffness. 228 Histological data concerning the longterm status of the coronary arteries in children who never had demonstrable abnormalities are few and difficult to interpret.…”
Section: Course After Kawasaki Disease Without Detectable Coronary Lementioning
confidence: 99%
“…75,77,228 Children with Kawasaki disease with normal coronary arteries also have been reported to have higher brachial-radial artery mean pulse wave velocity than do children without Kawasaki disease, suggesting increased arterial stiffness. 228 Histological data concerning the longterm status of the coronary arteries in children who never had demonstrable abnormalities are few and difficult to interpret. 223,229 Some investigators in Japan have studied coronary physiology in the population without aneurysms.…”
Section: Course After Kawasaki Disease Without Detectable Coronary Lementioning
confidence: 99%
“…In Familial Mediterranean Fever [12], and even after resolved vasculitis in Kawasaki's disease, elevated baPWV is present [18]. Andoh et al [19] found a correlation between baPWV and high sensitivity C-reactive protein (hs-CRP) in Japanese men.…”
Section: Mechanistic Links Of Pwv To Acute and Chronic Diseasementioning
confidence: 99%